TECHNIQUE OF THERAPEUTIC EFFECT OF LOW-INTENSITY LASER RADIATION IN CASE OF ORAL TRAUMA - Kamalova Mekhriniso Kilichevna; Sharipova Gulnihol Idievna (Scholar Express Journals, 2021)
Currently, hundreds of methods have been developed for the treatment and prevention of recurrence of many diseases, including in dentistry. Laser therapy technologies are easy to implement, do not require expensive equipment, are effectively combined with almost all other methods of treatment (both therapeutic and surgical), so they can be used in their work by any practicing dentist, not just a physiotherapist. The book presents both a review of the literature on the topic and the most effective scientifically grounded methods of combined and combined laser therapy.
Keywords: low-intensity laser radiation; epithelium; prevention; treatment